MAJAS DALAM BERITA REDAKSIANA DI TRANS 7 DAN IMPLIKASINYA TERHADAP PEMBELAJARAN - Erika Pratiwi; Siti Samhati (FKIP Universitas Lampung, 2016)
The problem in this research was the use of figurative language, the function of the figurative language in Redaksiana news in Trans 7, and its implication to learn the Indonesian language at high school. The purposes of this research were to describe the figurative language, the function of the figurative language in Redaksiana news in Trans 7, and to verify the implication of the figurative language in learning Indonesian language at high school. This research used qualitative descriptive method. Based on the analysis result the researcher concluded the figurative language used covered alliteration, assonance, erotecis, hyperbole, paradox, equation, a metaphor, personification, and eponym. Figurative language which is the most dominant used was assonance. The function of the figurative language were to excite the atmosphere, excite the impress on deep, affirmation, and increase the aesthetic effect on it. The implication of the figurative language in the learning in school was in analyzing short story text (the adiction, the language use, and conjuction) carefully.Masalah penelitian ini adalah penggunaan majas, fungsi majas yang terdapat dalam berita Redaksiana di Trans 7, dan implikasinya terhadap pembelajaran bahasa Indonesia di SMA. Tujuan penelitian ini untuk mendeskripsikan majas, fungsi majas dalam berita Redaksiana di Trans 7, dan implikasinya terhadap pembelajaran bahasa Indonesia di SMA. Metode yang digunakan adalah metode deskriptif kualitatif. Berdasarkan hasil analisis, penulis menyimpulkan adanya penggunaan majas meliputi aliterasi, asonansi, erotesis, hiperbol, paradoks, persamaan, metafora, personifikasi, dan eponim. Majas yang paling dominan digunakan adalah asonansi. Fungsi majas meliputi membangkitkan suasana, membangkitkan kesan mendalam, penegasan, dan menambah efek estetis. Implikasi majas terhadap pembelajaran di sekolah berupa menganalisis teks cerita pendek (pilihan kata, gaya bahasa, dan konjungsi) dengan cermat.Kata kunci : berita, majas, pembelajaran.